2014
DOI: 10.1016/j.ijgo.2014.05.018
|View full text |Cite
|
Sign up to set email alerts
|

Demand and supply factors affecting the rising overmedicalization of birth in India

Abstract: Synopsis:After controlling for risk factors and socioeconomic characteristics, the probability of cesarean delivery in India was driven mainly by supply factors rather than by demand. ABSTRACTObjective: To understand the interaction between health systems and individual factors in determining the probability of a cesarean delivery in India. Methods:In a retrospective study, data from the 2007-2008 District Level Household and Facility Survey was used to determine the risk of cesarean delivery in six states (Pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2015
2015
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
2
18
0
Order By: Relevance
“…Some studies indicated that the caesarean section rate is higher in the private sector as is in our study. 4,6,7,9,16 The vaginal birth after caesarean rate in our study was 16.8% similar to those in the private sector of the same region 7 in contrast to other studies, which had success rates between 60 and 78%. 10,17,18 This is due to a very high rate of repeat caesarean section on maternal request (33.8% -36.07%) in both the studies.…”
Section: Fig 1: Flow Of Study Participantssupporting
confidence: 60%
See 1 more Smart Citation
“…Some studies indicated that the caesarean section rate is higher in the private sector as is in our study. 4,6,7,9,16 The vaginal birth after caesarean rate in our study was 16.8% similar to those in the private sector of the same region 7 in contrast to other studies, which had success rates between 60 and 78%. 10,17,18 This is due to a very high rate of repeat caesarean section on maternal request (33.8% -36.07%) in both the studies.…”
Section: Fig 1: Flow Of Study Participantssupporting
confidence: 60%
“…Rates of caesarean section for maternal request appear to correspond with age, higher socioeconomic status and educational attainment. 16,19,20 This group is underreported in most studies and not represented adequately in any of the Robson or modified Robson groups. 14,21 Systematic reviews of randomised control trials, which provided various forms of decision support interventions including prenatal information, support and cognitive therapy failed to show any significant benefit in decision making about mode of delivery in women with a previous caesarean section.…”
Section: Fig 1: Flow Of Study Participantsmentioning
confidence: 99%
“…The present study found a significant relationship between induced demand and the related factors of knowledge and awareness of service recipients, sensitivity of clients toward their own health, monitoring and planning of insurance companies, personal interests of service providers, industrialization of the healthcare sector, increases in the variety and number of specialists, knowledge and awareness of service providers, quality of education models and training methods for service providers. Leone conducted a study in three provinces of India in 2014, which indicated the role of several factors in induced supply and demand 30 . The present study is also in line with a study by Keyvanara et al, which demonstrated factors such as the role of supplemental health insurance, lack of strict supervision on insurance companies, increased profit of equipment companies, diagnostic centers, pharmaceutical companies, the over-trusting of physicians, incorrect demands of patient from the physicians, lack of awareness, patients' free access to physicians, patients' willingness to make greater use of free services and franchising affect the incidence of induced demand 4 .…”
Section: Discussionmentioning
confidence: 99%
“…Another research described that many factors are involved in C-Section [14]. Major factors for C-Section delivery showed the relationship between section birth, wealth, education, age, ultrasonography, pregnancy completions.…”
Section: Literature Reviewmentioning
confidence: 99%